2021
DOI: 10.3390/s21041333
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy-Based Quality Control of “Silicon-On-Insulator” Nanowire Chips for the Detection of Brain Cancer-Associated MicroRNA in Plasma

Abstract: Application of micro-Raman spectroscopy for the monitoring of quality of nanowire sensor chips fabrication has been demonstrated. Nanowire chips have been fabricated on the basis of «silicon-on-insulator» (SOI) structures (SOI-NW chips). The fabrication of SOI-NW chips was performed by optical litography with gas-phase etching. The so-fabricated SOI-NW chips are intended for highly sensitive detection of brain cancer biomarkers in humans. In our present study, two series of experiments have been conducted. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…oDNA molecular probes were covalently immobilized onto the APTES-modified surface of the sensor chip via DTSSP crosslinker using the technique reported in our previous papers [ 33 , 34 , 35 , 36 , 37 ]. The concentration of the oDNA probes in the immobilization solution, prepared using 50 mM potassium phosphate buffer (pH 7.4), was 1 μM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…oDNA molecular probes were covalently immobilized onto the APTES-modified surface of the sensor chip via DTSSP crosslinker using the technique reported in our previous papers [ 33 , 34 , 35 , 36 , 37 ]. The concentration of the oDNA probes in the immobilization solution, prepared using 50 mM potassium phosphate buffer (pH 7.4), was 1 μM.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the data obtained in these experiments has indicated that upon repeated analysis of one and the same sample, changes in the signal from the NS sensitized with probe #1 (Figure 9а) make up ~40%, while the signal was virtually unchanged in the case with the NS sensitized with probe #4 (Figure 9b). Thus, the previously developed technique for the regeneration of the SOI-NS sensor surface allows for the repeated use of the SOI-NS sensor chip in the analysis of biological fluids [33][34][35][36][37]. The experiment on the analysis of one and the same miRNA sample isolated from plasma of a patient with confirmed ASD diagnosis was being performed for two working days.…”
Section: Biospecific Detection Of Mirnas Isolated From Blood Plasmamentioning
confidence: 99%
“…The system used for plasma samples was surface-modified with miRNA-363 itself. Overall, the sensor was sensitive, starting from a concentration level of 3.3 × 10 –17 M. 23 …”
Section: Raman Spectroscopy In Diagnosismentioning
confidence: 99%
“…These fabricated chips were used to detect miRNA-363 first in purified buffer solution and later in human plasma, which has been associated with brain tumours. 9 Livermore et al, compared intraoperative tumour identification beyond contrast margin with RS and 5-aminolevulinic acid (5-ALA) induced fluorescence. In glioblastoma, RS had a significantly better predictive value than 5-ALA induced fluorescence and RS outperformed 5-ALA in detecting infiltrative tumour in areas with no fluorescence.…”
Section: Review Of Evidencementioning
confidence: 99%